2016
DOI: 10.1002/job.2124
|View full text |Cite
|
Sign up to set email alerts
|

Leadership, followers' mental health and job performance in organizations: A comprehensive meta‐analysis from an occupational health perspective

Abstract: Summary The present meta‐analysis investigates the associations between leadership, followers' mental health, and job performance by taking into account different groups of leadership constructs including transformational leadership, relations‐oriented leadership, task‐oriented leadership, destructive leadership, and leader–member exchange. Six categories of mental health‐related outcomes are considered representing both negative and positive mental health states of followers, namely, affective symptoms, burno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
346
1
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(428 citation statements)
references
References 141 publications
24
346
1
12
Order By: Relevance
“…They, however, suggested the employee-related variables that have been shown to mediate the HPWS-performance relationship as providing an opportunity to explore mutuality in the employment relationship. A similar observation can be made in the leadership literature as the performance implications of leadership have been explicated in terms of employee-related variables (Nielsen & Munir, 2009) and increasingly, in terms of well-being (Gubler et al, 2017;Montano et al, 2017). Donaldson-Feilder et al's (2013, p. 168) call for research to "create a much clearer understanding of the complexity of the relationship that exist between leadership, employee well-being, and performance" underscores the need for a unifying framework.…”
Section: Theoretical Implicationssupporting
confidence: 62%
See 1 more Smart Citation
“…They, however, suggested the employee-related variables that have been shown to mediate the HPWS-performance relationship as providing an opportunity to explore mutuality in the employment relationship. A similar observation can be made in the leadership literature as the performance implications of leadership have been explicated in terms of employee-related variables (Nielsen & Munir, 2009) and increasingly, in terms of well-being (Gubler et al, 2017;Montano et al, 2017). Donaldson-Feilder et al's (2013, p. 168) call for research to "create a much clearer understanding of the complexity of the relationship that exist between leadership, employee well-being, and performance" underscores the need for a unifying framework.…”
Section: Theoretical Implicationssupporting
confidence: 62%
“…For example, research has shown that implementation of high‐performance work systems (HPWS) leads to work intensification and ultimately, impairs employee physical and psychological health (Kroon, Van De Voorde, & Van Veldhoven, ; Loon, Otaye‐Ebede, & Stewart, ; Ogbonnaya, Daniels, Connolly, & Van Veldhoven, ; Van De Voorde, Paauwe, & Van Veldhoven, ). Similarly, leadership behaviours such as abusive supervision has been shown to impair employee well‐being (Liang, Hanig, Evans, Brown, & Lian, ), precipitating a growing focus on well‐being in the wider leadership literature (Donaldson‐Feilder et al, ; Inceoglu, Thomas, Chu, Plans, & Gerbasi, ; Jiménez, Winkler, & Dunkl, ; Kelloway & Barling, ; Kelloway, Turner, Barling, & Loughlin, ; Kelloway, Weigand, McKee, & Das, ; Montano, Reeske, Franke, & Huffmeier, ).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, the supervisor in charge may play another important role. Extensive research has been performed on the influence of supervisor behavior and leadership style on employees' work performance and well-being [32][33][34]. Data show that both can be related to workers' mental health in a negative or positive way.…”
Section: Introductionmentioning
confidence: 99%
“…Whether called thriving, flourishing, prospering, or actualization, organizations have the capacity to shape healthy identities (Dailey & Zhu, 2017) and foster well‐being. Applied research in this area pertains more to organizational‐level efforts (e.g., policies, practices, and benefits) that: (a) promote work‐life balance, wherein employee roles inside and outside of work enrich and enhance the other, partly through human resource benefits (Muse, Harris, Giles, & Feild, ; Kossek, Valcour, Lirio; 2014); (b) enhance happiness at work (Amabile & Kramer, ; Nielsen et al, 2017; Nierenberg, Alexakis, Preziosi, & O’Neill, 2017; Simmons, ); (c) promote positive leadership behaviors such as virtue, servant and transformational leadership, and healthy role modeling (e.g., Kelloway, Weigand, McKee, & Das, ; Kuoppala, Lamminpää, Liira, & Vainio, ; Montano, Reeske, Franke, & Hüffmeier, ; Van Dierendonck, Haynes, Borrill, & Stride, ); and (d) build positive psychological resources such as mindfulness, work breaks, positive reflection, and gratitude in the work setting (Gilbert, Foulk, & Bono, ; Virgili, ). A meta‐analysis of randomized trials of positive psychological interventions (39 studies, n = 6,139) showed positive effects of these types of efforts on improved well‐being and reduced depression (Bolier et al., ).…”
Section: Part 2—elements Of Integral Modelmentioning
confidence: 99%